Revisiting Pound's Law in Action and Ehrlich's Living Law to Find the "Gap": A Compilation of Lecture Notes - David Tan (Journal of Judicial Review, 2022)
Finding research "gap" is an important aspect that must always be done when starting research. Especially if the research is a sociological research. This article aims to shed light on the sociological approach in legal research into approaches, namely the Sociology of Law approach and the approach of Socio-legal Studies. These two approaches have different and unique ways of defining research "gaps" This article will examine using empirical methods that rely on primary and secondary data, as well as inductive methods to analyze data. A comparison will also be made between Ehrlich's "living law" and Pound's "law in action" so that the differences between the two ideas can be found so that in the future, future researchers will not consider the two ideas identical.